Hubungan Kualitas Tidur Terhadap Kebugaran Jasmani Siswa Kelas VIII SMP Negeri 3 Bajo - Faudiansyah, Muh; Jalil, Rasyidah; Pribadi, Imam (Jurnal Porkes, 2025)
The purpose of this study was to determine the relationship between sleep quality and students' physical fitness. This study is a correlational study using the survey method with instruments in the form of measurement tests, sleep quality instruments using the pittsburgh sleep quality index (PSQI) questionnaire with validity (r = 0.73), reliability (cronbach's a = 0.83), while cardiorespiratory physical fitness using the multistage fitness test (MFT) test with validity (r = 0.71), test reliability (0.521). The population of this study were grade VIII students at SMPN 3 Bajo. The sampling technique was purposive random sampling. The total sample was 24 students. Data analysis using product moment correlation (karl pearson) at a significance level of 0.05 or 5%. Based on the results of data analysis, description, and testing of the research results, the value of rx.y = 0.517 > 0.05, r table = 0.517. significance is less than 0.05 (0.000 < 0.05) or the value of deviation from linearity is greater than alpha 0.05 (0.224 > 0.05), it can be concluded that between the fitness and sleep quality variables there is a linear relationship. So it can be concluded that there is a significant relationship between sleep quality and physical fitness of class VIII students at State Junior High School 3 Bajo.